Statistical analysis of determining the reproducibility of the study of the developed test system for detecting African swine fever virus DNA (Nexo Revista Científica, 2023)
The study aimed to develop a loop-mediated isothermal amplification-based test system with hybridization-fluorescence detection to detect the DNA of the African swine fever virus in the presence of an internal control sample. As part of the study, optimal amplification conditions were determined, a method of nucleic acid extraction was selected, and the amplification of positive and negative samples was analyzed. Statistical analysis was carried out to determine the reproducibility of the study of the developed test system. The genetic features of the African swine fever virus were studied, and the most promising fragment of the genome for the specific identification of this pathogen, the major capsid protein p72 gene, was identified. Oligonucleotides were selected for isothermal amplification of the target. The results of the study are valuable from the point of view of further developments in virology, epidemiology, and diagnostics and can also be used by organizations and institutions involved in the control and prevention of animal diseases, in particular African swine fever.